2009
DOI: 10.4103/0019-5154.53185
|View full text |Cite
|
Sign up to set email alerts
|

Childhood vitiligo : Response to methylprednisolone oral minipulse therapy and topical fluticasone combination

Abstract: Background:Childhood vitiligo is always a challenge to treat, especially when the disease is progressing rapidly in such a patient. Oral minipulse with betamethasone has been tried in childhood vitiligo and also in some other immune mediated skin disorders with good results.Aims:The aim of the present study was to see the overall efficacy of methylprednisolone oral minipulse therapy in combination with topical fluticasone in progressive childhood vitiligo. The combination was tried to achieve a significant amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 8 publications
0
23
0
2
Order By: Relevance
“…In this form of treatment, oral corticosteroids are given on two consecutive days every week with a 5-days rest between the two minipulses. [1215] The dose of betamethasone that has been used in this form of therapy is 5 mg on each of the 2 days in adults[13] while as methylprednisolone is used in a dose of 0.8 mg/kg body weight (max 32 mg) on each day of the minipulse. [12] The treatment is thus continued in most cases for duration of 6 months after which the treatment is usually withdrawn.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this form of treatment, oral corticosteroids are given on two consecutive days every week with a 5-days rest between the two minipulses. [1215] The dose of betamethasone that has been used in this form of therapy is 5 mg on each of the 2 days in adults[13] while as methylprednisolone is used in a dose of 0.8 mg/kg body weight (max 32 mg) on each day of the minipulse. [12] The treatment is thus continued in most cases for duration of 6 months after which the treatment is usually withdrawn.…”
Section: Introductionmentioning
confidence: 99%
“…[1215] The dose of betamethasone that has been used in this form of therapy is 5 mg on each of the 2 days in adults[13] while as methylprednisolone is used in a dose of 0.8 mg/kg body weight (max 32 mg) on each day of the minipulse. [12] The treatment is thus continued in most cases for duration of 6 months after which the treatment is usually withdrawn. The treatment is advocated in patients with progressive patchy or generalized vitiligo and even in acrofacial vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported the use of oral MPD (0.8 mg/kg, maximum dose of 32 mg) given on 2 consecutive days a week for 6 months in progressive childhood vitiligo [13]. Four hundred children were enrolled, and more than 90% of the children went into complete remission whereas 65% achieved good to excellent repigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…In a later study on childhood vitiligo, betamethasone was replaced by oral methylprednisolone and combined with topical fluticasone ointment on the vitiligo lesions. The disease was arrested in >90% of patients, and >65% of children achieved good to excellent (>50%) repigmentation of their vitiligo lesions 29 .…”
Section: Systemic Immunomodulator Therapymentioning
confidence: 99%
“…This has been further proved by the demonstration of receptors for 1 alphadihydroxyvitamin D3 on the melanocytes. These receptors are believed to have a role in stimulating melanogenesis 29 . Vitamin D analogues have given variable results in the treatment of vitiligo in different studies.…”
Section: Topical Vitamin D Analoguesmentioning
confidence: 99%